Inter-relação do iodo e do flúor no metabolismo de ovinos jovens - Prestes, Danívia Santos (2007)
Mineral supplementation of is a well-known factor contributing to productivity in sheep or cattle herds. However, little is known about mineral interactions in these species. The objective of the present work was to evaluate the inter-relation of iodine (I) and fluoride (F) in young ovine metabolism and the thyroid gland. Two experiments were conducted; first it was analyzed the dynamics of urinary I excretion in sheep. Five lambs were used in a repeated measurement protocol. After a 15-day adaptation period urine samples were collected (control group), then animals received 3 different 15-day treatments (0,05; 0,42; and 0,8 mg of I/kg DM) consecutively. Punctual (8 hour interval) and 24 hour total urine samples were collected. No differences in I excretion among treatments or collection time. Also, there were no differences in urinary creatinine levels among treatments or collection time, except between 16:00 and 24:00 hours in the medium dose. No significant correlation was found between urinary I and creatinine. In a second experiment, it was evaluated the effect of chronic fluoride administration in thyroid function and histology in sheep. Twelve ram lambs were allocated into 2 groups: Control which received 5g NaCl + 0,2 mg of I/Kg DM and treated group which received the same treatment plus sodium fluoride (4,7 mg F/ Kg BW) daily for 150 days. Blood samples were collected at 60, 90, 120, and 150 days for determination of F, I T3 and T4. At the same time points, total 24-hour urine production was collected for measurement of F and I. After euthanasia, at 150 days of treatment, thyroid gland was removed for histopathological and morphometrical analyses. No differences were found between or within groups for urinary I. Also no differences were found for T3 and T4 nor serum I between groups or among time points. No histological alterations were found in the thyroid. In conclusion, urinary I excretion is not a reliable parameter to access I status in animals with supplementation within the recommended levels. Additionally, data related to Iodine-fluoride interactions cannot be used across species, since the effect of fluoride on the thyroid appears to have specie dependant intensity